Digitalisasi Sistem Monitoring Kedisiplinan Siswa Menggunakan Pendekatan Human Centered Design untuk Meningkatkan Transparansi Sekolah - Shofiyah Nur Jannah; A. Ferico Octaviansyah Pasaribu (Institut Teknologi Garut, 2026)
Digital transformation in education has become an essential requirement for improving data management efficiency and information transparency in the era of Industry 4.0. MTs Al-Ikhlas continues to face challenges in monitoring student discipline, as records of violations and achievements are still maintained manually using physical record books. This condition increases the risk of data loss, reporting inaccuracies, and delays in delivering information to relevant stakeholders. This study aims to design the User Interface (UI) and User Experience (UX) of the E-POIN application as a digital student discipline monitoring system using the Human-Centered Design (HCD) approach. The HCD methodology applied in this research consists of three main phases: Inspiration, Ideation, and Implementation. During the Inspiration phase, observations and interviews were conducted with Guidance and Counseling (GC) teachers and parents to identify user needs. The Ideation phase involved the development of wireframes and high-fidelity designs tailored to user requirements and school regulations. Subsequently, the Implementation phase was carried out through prototype testing using the System Usability Scale (SUS) method, involving 10 respondents consisting of 3 GC teachers and 7 other teachers. The results indicate that the proposed E-POIN application successfully provides digital features for recording student violations and achievements, integrated data monitoring, and notification services for parents via WhatsApp. Usability testing demonstrated a task completion rate of 100% and an average SUS score of 85, which falls within the Excellent category. These findings suggest that the Human-Centered Design approach is effective in producing an application design with a high level of usability and strong alignment with user needs within the MTs Al-Ikhlas educational environment.